Smart Desa, Layanan Cerdas : Inovasi Digitalisasi Pelayanan Administrasi di Desa Sabrang, Klaten - Purbo Briyadi; Amirul Mustofah; Ika Devy Pramudiana (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study examines the digital transformation of administrative services in Sabrang Village, Klaten, as part of the Smart Village initiative. The integration of Information and Communication Technology (ICT) aims to enhance service efficiency, transparency, and accountability at the village level. The research highlights the implementation of online platforms for administrative processes, such as issuing certificates and permits, and the use of real-time notification systems to monitor application statuses. Additionally, efforts to improve digital literacy among village officials and the community are emphasized to ensure successful adoption. The study underscores the importance of structured policies, capacity building, and community engagement in realizing the benefits of digitalization. While challenges such as limited infrastructure and resistance to change persist, the digitalization of village administration is shown to significantly increase service speed, reduce bureaucratic hurdles, and foster participatory governance. Ultimately, digital transformation in rural governance can support the creation of a more inclusive, efficient, and transparent local government, contributing to broader development goals.